Decomposition characteristics of humic acid in boiler make-up water in power plants. (5th January 2018) - Zhu, Zhiping; Qiao, Yue; Wang, Nana; Cao, Jie
Highlights: Decomposition products of humic acid exert an influence on the pH values. Inorganic ions in decomposition products of humic acid are Cl −, SO4 2−, NO3 − and F − . TOC of the make-up water should be strictly controlled. Abstract: The organic matter (OM) entering the water–steam cycle of a power plant has been considered as one potentially serious contaminant in the industry. Therefore, the thermal decomposition characteristics of humic acid (HA) were investigated at an elevated temperature in a stainless steel autoclave through ion chromatography and total organic carbon analysis methods. The concentrations of the impurity anions varied with the changes in HA concentration and pyrolysis time. In addition, the different contents of thermal decomposition products in the vapour–liquid environment were evaluated. Results show that the major inorganic decomposition products of humic acid at 350 °C are chloride, sulfate, nitrate and fluoride ions. The experimental results are expected to contribute significantly to the quality control of feed and make-up water in power plants.